Application of the Intracellular Gamma Interferon Assay To Recalculate the Potency of CD8(+) T-Cell Responses to Herpes Simplex Virus - Kumaraguru, Udayasankar (American Society for Microbiology, 2000)
Enumeration and characterization of herpes simplex virus (HSV)-specific CD8(+) T lymphocytes are tedious and indirect. We quantitated antigen-specific CD8(+) T cells during acute and secondary stages of HSV infection using intracellular gamma interferon production upon stimulation with virus or immunodominant peptide. Results show a substantial increase in the number of CD8(+) T cells which was otherwise underestimated with the conventional limiting dilution analysis.